Effect of CAR, NPL, and BOPO on NIM with ROE as a moderating variable - Widana, I Wayan Dedik; Yasa, Gerianta Wirawan; Suaryana, I Gusti Ngurah Agung (International research journal of management, IT and social sciences, 2021)
This study aims to obtain empirical evidence about the effect of CAR, NPL and BOPO on NIM and examine the role of ROE in moderating the effect of CAR, NPL, and BOPO on NIM. This study uses purposive sampling method. The data used is secondary data obtained from the financial statements of banking companies listed on the Indonesia Stock Exchange in the 2015-2019 period. Data analysis techniques using moderated regression analysis (MRA) test. The result of the analysis shows that CAR has a positive effect on NIM. NPL and BOPO has a negative effect on NIM. The moderating variable ROE strengthens the effect of CAR on NIM but weakens the effect of NPL and BOPO on NIM.